Recursos didácticos y su influencia en el proceso de enseñanza virtual de los docentes de la unidad educativa Adolfo María Astudillo, Babahoyo, 2021 - Nivela Morales, Juletsy Jusseth (2021)
This project was carried out in order to study didactic resources and their influence on the virtual teaching process of teachers. It aims to diagnose what role the educational institution plays in the use of didactic resources for the process of virtual teaching of the teachers, Identify the benefits of using teaching resources for the virtual teaching process, Analyze the factors that influence the relationship between the use of didactic resources and the virtual teaching process of teachers, Determine the influence generated by the use of didactic resources in the virtual teaching process of teachers. The procedure of a non-empirical design was applied by applying the deductive - inductive method, of non-experimental modality of applied, descriptive, causal type in the Educational Unit Adolfo Maria Astudillo. Through the survey that was directed to 30 teachers, it resulted that a large part of the population taken agrees on the implementation of recordings, posters, change traditional teaching using teaching materials, others are totally in agreement with energizing classes using tics as tools that potentiate classes, in itself, the didactic resources allow to organize and facilitate teaching, guaranteeing an optimal development in the students, and even platforms allow them to have better interactivity. In short, virtual teaching materials have as fundamental objectives to offer coverage to learning needs and skills of the students and the educational and epistemological variety of these, allowing stimulation, communication, participation, interaction and innovation